Zigbee light link and its applicationss - Wang, Jianfeng (IEEE wireless communications, 2013)
The lighting industry has been going through fundamental digital revolution: with light sources going for LED, drivers going digital, and control going networked. This revolution creates the flush of energy-efficient and modern-designed home lights, and also frees up the way of using lights together with the proliferation of smart devices, sensors, and internet of things. The control of lights becomes fast and rich-flavored, going beyond on/off, dimming, to color (or color temperature) change and scene setting, with intelligence to react to human mood and activity, and adapt to environments. To fully explore the benefits of the new generation lights, the last hop (x10 meters) connectivity is key. ZigBee Light Link (ZLL) [1] gives the lighting industry a global communication standard for interoperable and very easy-to-use consumer lighting and control products. It allows consumers to gain wireless control over all their LED fixtures, light bulbs, timers, remotes and switches. Products using this standard will let consumers change lighting remotely to reflect ambiance, task or season, all while managing energy use and making their homes greener.